2022
DOI: 10.21203/rs.3.rs-1878371/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cardiac Magnetic Resonance Feature Tracking Myocardial Strain Analysis in Suspected Acute Myocarditis: Diagnostic Value and Association with Severity of Myocardial Injury

Abstract: Background: Albeit that cardiac magnetic resonance feature tracking (CMR-FT) has enabled quantitative assessment of global myocardial strain in the diagnosis of suspected acute myocarditis, the cardiac segmental dysfunction remains understudied. The aim of the present study was using CMR-FT to assess the global and segmental dysfunction of the myocardium for diagnosis of suspected acute myocarditis.Methods: 47 patients with suspected acute myocarditis (divided into impaired and preserved left ventricular eject… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Cardiac magnetic resonance (CMR) imaging with Gadovist® contrast was performed on a Vantage Titan HSR 1.5 Tesla scanner (Toshiba, Japan). Images of the heart were evaluated along the short and long axes in three modes: T1 -(to detect hyperemia in the area of the inflammatory lesion), T2 -(to detect areas of edema) and late gadolinium enhancement (LGE) mode (10-15 minutes after contrast injection to detect necrotic or fibrotic changes) [8,12,13]. The severity of myocardial edema was evaluated, and a quantitative analysis of the areas of contrast accumulation in the early and delayed phases was performed according to the standardised imaging of the 17-segment structure of the LV myocardium with an assessment of the number of segments with inflammatory and fibrotic changes [8,10].…”
Section: Methodsmentioning
confidence: 99%
“…Cardiac magnetic resonance (CMR) imaging with Gadovist® contrast was performed on a Vantage Titan HSR 1.5 Tesla scanner (Toshiba, Japan). Images of the heart were evaluated along the short and long axes in three modes: T1 -(to detect hyperemia in the area of the inflammatory lesion), T2 -(to detect areas of edema) and late gadolinium enhancement (LGE) mode (10-15 minutes after contrast injection to detect necrotic or fibrotic changes) [8,12,13]. The severity of myocardial edema was evaluated, and a quantitative analysis of the areas of contrast accumulation in the early and delayed phases was performed according to the standardised imaging of the 17-segment structure of the LV myocardium with an assessment of the number of segments with inflammatory and fibrotic changes [8,10].…”
Section: Methodsmentioning
confidence: 99%
“…Recent adult studies have shown correlation between myocarditis diagnosis and echocardiographic global and segmental myocardial strain abnormalities, which gives promise to the possibility of echocardiographic diagnosis and follow-up of myocarditis [58 ▪ ,59]. Strain evaluation by CMR has also shown diagnostic value in myocarditis and may help improve future diagnostic criteria for pediatric myocarditis [60 ▪▪ ,61]. Additionally, positron emission tomography (PET) of increased myocardial metabolic activity has been used to evaluate myocarditis, with suggestion that this technology may provide improved prognostic ability in follow-up evaluations as well as significant utility in myocarditis mediated by systemic inflammatory or rheumatologic disorders [62,63].…”
Section: Cardiac Magnetic Resonance Imagingmentioning
confidence: 99%